PERAN CITRA DESTINASI DALAM MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN - Dimas Yudistira Nugraha (BISMA: Jurnal Bisnis dan Manajemen, 2021)
This study examines the relationship between destination image and intentions to revisit tourism attractions. The conceptual model was developed and then tested using data collected from tourists visiting cultural heritage sites in Bali. The sample used in this study was 300 respondents. Researchers used a Structural Equation Modeling (SEM) to analyze the data. The results showed that destination image significantly affected revisit intentions. This research implies that the local tourism business owners need to increase the attractiveness of local culture to improve destination image so that tourists will get a distinguished experience compared to other tourist attractions